HUBUNGAN LAMA PEMAKAIAN KONTRASEPSI SUNTIK DEPO PROGESTIN DENGAN KENAIKAN BERAT BADAN - Tiara Fatma Kumala (Universitas Duta Bangsa Surakarta, 2021)
Background : Depot Medroxy Progesterone Acetate (DMPA) 150mg or depot progestin is injected every 3 months. This injectable contraceptive is commonly used in Indonesia, according to the BKKBN, there are 2,186,003 (47.65%). Injectable contraceptives have side effects including weight changes. The purpose of this study was to determine the relationship between duration of use of depo progestin injection contraceptives with weight gain in injection acceptors. Research Methods: This type of research uses retrospective analysis. The sampling technique is purposive sampling. The samples studied were all acceptors of depo progestin injections as many as 50 respondents. The data collection technique used a checklist to collect data on contraceptive use and weight gain. Results: Based on data analysis, 30 acceptors (60%) used Depo Progestin contraception for more than 3 years, and 31 acceptors (62%) used Depo Progestin injectable contraception. There is a difference in weight gain between respondents who have used Depo Progestin injection contraceptives for 1 year and used Depo Progestin injection contraceptives for > 1 year. The results obtained by the value of X2count>X2table are 6.848>3.841 with p<0.05, which means that there is a relationship between duration of use of progestin-depo injection contraception and weight gain. Conclusion : There is a significant relationship between duration of use of depo progestin injection contraception and weight gain